Sementes de ciência: livro de homenagem a António Marinho Amorim da Costa - Hugh D. Burrows (Documentos, 2011)
In recognition of António Amorim da Costa's important contributions to history of science, the various chapters of this book by his friends and colleagues cover topics related to the prehistory of chemistry, alchemy, iatrochemistry, the phlogiston period, pneumatic chemistry and more recently the history of quantic chemistry and statistical mechanics, with particular emphasis upon the historical development of chemistry in Portugal and Brazil.ALT_QUEBRA_LINHAHowever, chemistry did not develop in isolation, and the contributions to this book also touch on neighbouring areas, such as electricity, medicine, optics and mineralogy. Neither do they deal exclusively with facts; people are also studied, such as the 18th century Luso-Brazilian engineer José Fernandes Pinto Alpoim, and the 19th century Portuguese chemist from the University of Coimbra, Thomé Rodrigues Sobral, and many more. It is hoped that these "pieces" of history of science will enrich our understanding of the field and acknowledge the contributions made by António Amorim da Costa to this area.